Perceived Motion Sickness and Effects on Performance Following Naval Transportation - Dahlman, J.; Falkmer, Torbjorn; Forsman, F. (The Society for Human Performance in Extreme Environments, 2012)
The present study focused on the relationship between previous experiences of, and rated susceptibility to, motion sickness and its correlation to subjective measurements and actual performance. Performance was measured in terms of shooting precision among 23 participants from the Swedish amphibious corps after transportation in a small amphibious boat, while sealed off with no reference to the outside world. Self-rating questionnaires were collected regarding perceived performance and presence of motion sickness. The physiological status perceived by each participant was related to factors that generally indicate early stages of motion sickness, which also were correlated to deficits in performance. It was further shown that participants who believed that their performance could be affected by motion sickness also performed less well.